1990
DOI: 10.1063/1.103160
|View full text |Cite
|
Sign up to set email alerts
|

Photon scanning tunneling microscope study of optical waveguides

Abstract: A novel technique, photon scanning microscopy, is shown to probe directly the evanescent field outside a planar and a channel waveguide. The decay lengths for these evanescent fields were measured and correspond well to the decay lengths of the evanescent fields calculated for each structure. Two-dimensional scanning at constant intensity or constant height reveals lateral variations in these fields due to topographic changes, index of refraction inhomogeneities, or modal variations within the waveguide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 6 publications
1
30
0
Order By: Relevance
“…A similar set-up, referred to as photon scanning tunneling microscope (PSTM), has been reported by Reddick et al [5] and Courjon et al [6]. The PSTM has been demonstrated in a spectroscopic mode [11] and applied to waveguides [12]. Although 5 nm lateral resolution has been claimed [6] caution should be taken in the interpretation of these images because of polarization effects and tip artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…A similar set-up, referred to as photon scanning tunneling microscope (PSTM), has been reported by Reddick et al [5] and Courjon et al [6]. The PSTM has been demonstrated in a spectroscopic mode [11] and applied to waveguides [12]. Although 5 nm lateral resolution has been claimed [6] caution should be taken in the interpretation of these images because of polarization effects and tip artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…83,93,94 In direct analogy to STM, the photon scanning tunneling microscope (PSTM) was demonstrated, which detected the evanescent waves on the boundary of a prism under total internal reflection with a bare, tapered optical fiber. [95][96][97][98][99][100] Shortly after, researchers demonstrated similar apertureless SNOM systems that used a nanoscale tip probe instead of an aperture probe. [7][8][9][10][11][12][13][14] This type of microscope is often constructed from an AFM with a cantilever tip that is formed of either a dielectric, semiconductor, or metal.…”
Section: A Apertureless Snom Conceptmentioning
confidence: 99%
“…NSOM studies of waveguides have demonstrated evanescent field decay [9], standing modes [10], and recently observed a modulation in the propagation direction [11] due to the Tien effect [12]. To the best of our knowledge, our measurements provide the first observation of standing modes in a single mode waveguide, as well as the first determination of all components of the propagation vector [13].…”
Section: Introductionmentioning
confidence: 63%